Electrical Dysfunction Associated with Conductor Externalization of a Silicone Left Ventricular Lead. Issue 3 (13th January 2015) - MENDENHALL, G. STUART; SABA, SAMIR
<x xml:space="preserve">Abstract</x> The St. Jude Medical QuickFlex LV lead family (St. Jude Medical, Inc., St. Paul, MN, USA) has been placed under advisory by the manufacturer due to a reported small number of cases of outer insulation failure and conductor externalization. There have been no reports of alteration of any electrical parameters associated with externalization. In this report, a sudden drop of impedance and rise in capture threshold of the left ventricular ring electrode is described, associated with the corresponding externalization of the inner conductor cables confirmed on physical examination. Flexion or torsion of lead was demonstrative of forces favoring externalization of inner conductor cables. Saline bath testing revealed a reproducible, transient reduction in lead resistance associated with conductor externalization. Close monitoring of electrical performance of this lead family is indicated.